How human resource managers can prevent perceived pandemic threats from escalating into diminished change-oriented voluntarism - De Clercq, D. (2022)
Purpose—For human resource (HR) managers, the harmful outcomes of employees’ ruminations about external crises, such as a pandemic, represent important, timely concerns. This research postulates that employees’ perceptions of pandemic threats might diminish the extent to which they engage in change-oriented voluntarism at work. This negative connection may be attenuated by employees’ access to two personal (work-related self-efficacy and organization-based selfesteem) and two relational (goal congruence and interpersonal harmony) resources. Design/methodology/approach—The theoretical predictions are tested with survey data collected among employees who work in a banking organization in Portugal. Findings—Persistent negative thoughts about a pandemic undermine discretionary efforts to alter and enhance the organizational status quo, but this detrimental effect is mitigated when employees (1) feel confident about their work-related abilities, (2) have a positive self-image about their organizational functioning, (3) share a common mindset with coworkers with respect to work goals, and (4) maintain harmonious relationships with coworkers. Practical implications—This study pinpoints several ways HR managers can reduce the danger that employees’ worries about life-threatening crises may lead to complacent responses that, somewhat paradoxically, might undermine their ability to alleviate the suffered hardships. Originality/value—The findings contribute to research on the impact of external crisis situations on organizations by providing an explanation of why employees may avoid productive, disruptive work activities, contingent on their access to complementary resources.